ANALISIS BENTUK KLITIK DALAM BAHASA SASAK DIALEK MENO-MENE - Sultana Sultana (Center of Language and Cultural Studies, 2017)
This study aims to determine the form, function and meaning of clitic in language Sasak of meno-mene dialect, using entholinguistic approach. Subjects of the study were Sasak people who spoke meno-mene dialect. Data were collected using observation, interview and introspection. Data were analyzed using constant comparative of intralingual analysis. Results of the study are as follows: (1) Form of clitic of Sasak language included phoneme /k/, /m/, /n/, /e/ and morpheme da, ta, na, KMO, and ko, (2) Preclitic: /K/, da, ta, na (3) Inclitic: /M/, /n/, /e/, KMO, and ko (4) Preclitic and inclitic; /K/, da, ta, and na, (5) Function of the clitic of Sasak language is to form pronouns in positive or negative senses, (6) Meaning of the clitic of Sasak language is to form singular and plural pronoun.